Simple and Feasible Detection of Hepatitis B Virus via Combination of Multienzyme Isothermal Rapid Amplification and Lateral Flow Dipstick Strip - Sun, Mao-Ling; Lai, Hai-Yun; Chong, Na-Yu; Liu, Dong-Fan; Zhang, Zhen-Yi; Pang, Bo; Yao, Jun (Frontiers in Molecular Biosciences, 2021)
Hepatitis B virus infection is not only a huge burden in the field of social health, but also a major public health problem that affects people’s lives and health. Simple, rapid, feasible detection of HBV is critical for its prevention and spread, especially in the developing countries with low-resource laboratories. To this end, we combined multienzyme isothermal rapid amplification (MIRA) and lateral flow dipstick (LFD) strip to detect HBV. A pair of primers targeting the conserved region of HBV genome was designed and used in MIRA-LFD assay. Our results found that the entire amplification of MIRA-LFD only takes 10 minutes at 37°C and the dilution of the amplification products was added in the LFD strip and observed by the naked eye after 10 min. The detection sensitivity of this method can reach 10pg. The 45 clinical samples were detected by MIRA-LFD and real-time PCR. The accuracy rate of MIRA-LFD was 100%. Therefore, these characteristics of our newly developed MIRA-LFD assay make it particularly useful and suitable for detecting HBV in the resource-limited condition.